2019
DOI: 10.7759/cureus.5591
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Radiotherapy Utilization for Lung Cancer Patients with Brain Metastases: A Population-based Analysis

Abstract: Introduction: Brain metastases occur in 15%-20% of lung cancer patients. Recently, studies have suggested that whole-brain radiotherapy (WBRT) may not prolong survival for a subset of patients, and is associated with significant side-effects. Furthermore, it is hypothesized that radiotherapy is often given near the end-of-life when the potential for benefit is minimal. Therefore, this study investigates how frequently radiotherapy for brain metastases is given near the end-of-life in a population-based cohort.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…reported a marked increase in SRS use from 7% in 2004 to 27% in 2014. The use of SRS for BM in patients with LC in a population‐based cohort in British Columbia, Canada, for a similar period (2014–2015), however, was much lower at around 11% 20 …”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…reported a marked increase in SRS use from 7% in 2004 to 27% in 2014. The use of SRS for BM in patients with LC in a population‐based cohort in British Columbia, Canada, for a similar period (2014–2015), however, was much lower at around 11% 20 …”
Section: Discussionmentioning
confidence: 97%
“…Several large single institutional studies in the UK, the United States and New Zealand have reported 30M following palliative RT for BM in the range of 11–23% 11–13 . In a Canadian population‐based study, Schlijper et al 20 . reported a longer time frame of 90‐day mortality following RT for BM of 40% in a cohort of 740 patients with LC in British Columbia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations